Proses dan Implementasi Kebijakan Publik dalam Organisasi Pemerintahan Daerah Kota Pariaman - Putri, Tiffany Melia; Jumiati, Jumiati; Saputra, Boni (CV. ITTC INDONESIA, 2025)
This research examines the public policy process in local government organizations in Pariaman City, focusing on how policies are made, who is involved, and the challenges or polemics that arise during the process. In addition, this research also describes the real practice in the field and how the policy is applied in people`s lives. By using a qualitative approach, including interviews with the Deputy Mayor of Pariaman for the 2024-2029 Period, observation, and literature related to public policy. This study found that the public policy process also faces various obstacles, both in terms of the demands of diverse community needs, coordination between institution, and limited community participation. The results of this study are expected to be input for local governments and communities so that they can jointly improve the process and implementation of public policy practices.